Etnoscience-based PBL using Subak Bali to shape elementary students' contextual science understanding - I Wayan Dresti Yasa; I Nyoman Jampel; I Nyoman Candiasa (Psychology, Evaluation, and Technology in Educational Research, 2025)
This study explores the implementation and challenges of the Etnoscience-Based Problem Based Learning (PBL) model using the Subak Bali Context in shaping science understanding (Force Material) in fourth-grade students at elementary school. Subak is analyzed as an etnoscience-rich irrigation system, providing an authentic context for Deep Learning according to the Merdeka Curriculum. This qualitative study uses a case study design. Data was collected through observation, interviews, and document analysis, including motivation questionnaire response patterns based on Uno's indicators and C4-C5 tests. Strict credibility procedures especially Source Triangulation and Member Checking were used for validation. The results show Etnoscience PBL is effective as a Deep Learning catalyst, evidenced by the C4-C5 narrative quality integrating the concept of Force. The implementation also fosters intrinsic motivation by fulfilling the students' Sense of Belonging. The main challenges found were cognitive focus management and cultural value sensitivity (Member Checking). Mitigation solutions include the Subak Miniature Model (low-cost) and C5 project revision for sustained motivation and HOTS.